2019
DOI: 10.3389/fnhum.2018.00525
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and Heart Rate Modulation Due to Competing Cognitive Tasks While Driving

Abstract: Research works on operator monitoring underline the benefit of taking into consideration several signal modalities to improve accuracy for an objective mental state diagnosis. Heart rate (HR) is one of the most utilized systemic measures to assess cognitive workload (CW), whereas, respiration parameters are hardly utilized. This study aims at verifying the contribution of analyzing respiratory signals to extract features to evaluate driver’s activity and CW variations in driving. Eighteen subjects participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
(54 reference statements)
2
34
0
Order By: Relevance
“…Respiration Features: From the respiration rate (RR) signal, arithmetic mean, standard deviation, and kurtosis are calculated as features in time domain. Similar to EEG, Welch’s method has been used to estimate the PSDs from the frequency ranges [0, 0.1], [0.1, 0.2], [0.2, 0.3], [0.3, 0.4], [0.4, 0.7], and [0.7, 1] [ 72 , 73 ]. The cognitive load has a distinct effect on the respiratory behaviour that can differ in sensitivity in the parameters obtained from respiratory signals [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiration Features: From the respiration rate (RR) signal, arithmetic mean, standard deviation, and kurtosis are calculated as features in time domain. Similar to EEG, Welch’s method has been used to estimate the PSDs from the frequency ranges [0, 0.1], [0.1, 0.2], [0.2, 0.3], [0.3, 0.4], [0.4, 0.7], and [0.7, 1] [ 72 , 73 ]. The cognitive load has a distinct effect on the respiratory behaviour that can differ in sensitivity in the parameters obtained from respiratory signals [ 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…The cognitive load has a distinct effect on the respiratory behaviour that can differ in sensitivity in the parameters obtained from respiratory signals [ 74 ]. According to Hidalgo-Muñoz et al [ 72 ] significant increases in the respiration rate are observed while driving in comparison to the base line condition. Moreover, the RR showed variations with a different level task difficulty and RR accelerated with an increasing cognitive workload.…”
Section: Methodsmentioning
confidence: 99%
“…Interval durations shorter than 0.5 s were considered as artifacts and removed. From the Fourier power spectrum of the filtered signal, the integrals in the frequency bands from 0.07 to 0.14 and 0.15 to 0.5 Hz, normalized by the total power, yielded spectral power features in the mid and high frequency bands, respectively (Hidalgo-Muñoz et al, 2018 ). RR parameters are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…1C). Initially, it was hypothesised that the higher HR response may have been the consequence of increased cognitive demand due to dual-tasking, 31 as participants were interpreting real-time information while maintaining their cycling work-rate. However, when HR responses were expressed relative to participants' maximal HR, these betweencondition differences were not observed.…”
Section: Discussionmentioning
confidence: 99%